Integrated Data Analysis of Six Clinical Studies Points Toward Model-Informed Precision Dosing of Tamoxifen - Klopp-Schulze, Lena; Mueller-Schoell, Anna; Neven, Patrick; Koolen, Stijn L. W.; Mathijssen, Ron H. J.; Joerger, Markus; Kloft, Charlotte (Frontiers in Pharmacology, 2020)
Introduction: At tamoxifen standard dosing, ~20% of breast cancer patients do not reach target endoxifen concentrations >5.97 ng/mL, determined by prior retrospective data analysis. Thus, a better understanding of causes of the large interindividual variability in tamoxifen pharmacokinetics is crucial. By applying nonlinear mixed-effects (NLME) modeling to a pooled ‘real-world’ clinical PK database, we aimed to (i) dissect several levels of variability and identify factors predictive for endoxifen exposure and (ii) assess different tamoxifen dosing strategies for their potential to increase the number of patients reaching target endoxifen concentrations. Methods: Tamoxifen and endoxifen concentrations with genetic and demographic data of 468 breast cancer patients were used to develop a NLME parent-metabolite pharmacokinetic model. Different levels of variability on model parameters or measurements were investigated and the impact of covariates thereupon explored. The model was subsequently applied in a simulation-based comparison of three dosing strategies with increasing degree of dose individualization for a large virtual breast cancer population. Interindividual variability of endoxifen concentrations and the fraction of patients at risk for not reaching target concentrations were assessed for each dosing strategy. Results & Conclusions: The integrated NLME model enabled to differentiate and quantify four levels of variability. Strong influential factors, i.e. CYP2D6 activity score, drug-drug interactions with CYP3A and CYP2D6 inducers/inhibitors and age, were reliably identified, reducing interoccasion variability to <20% CV. Yet, unexplained interindividual variability in endoxifen formation remained large (47.2% CV). Hence, therapeutic drug monitoring seems a promising strategy to ensure achievement of endoxifen target concentrations. Three tamoxifen dosing strategies (standard dosing (20 mg QD), CYP2D6-guided dosing (20 mg, 40 mg, 60 mg QD) and individual model-informed precision dosing (MIPD) (5-120 mg QD) were compared, leveraging the model. The proportion of patients at risk not reaching target concentrations was 22.2% in standard dosing, 16.0 % in CYP2D6-guided dosing and only 7.19% in MIPD. While in CYP2D6-guided- and standard dosing interindividual variability in endoxifen concentrations was high (64.0% CV and 68.1% CV, respectively), it was considerably reduced in MIPD (24.0% CV). Hence, MIPD demonstrated to be the most promising strategy for achieving target endoxifen concentrations with minimal unexplained interindividual variability.